Functional response and predation rate of Amblyseius swirskii (Acari: Phytosei-idae) at three constant temperatures - Ferdows Rafizadeh Afshar; Malihe Latifi (Persian Journal of Acarology)
Functional response and predation rate of Amblyseius swirskii (Athias-Henriot) on eggs of Tetranychus urticae Koch were determined on strawberry under laboratory conditions (70 ± 10% R.H. and 16L:8D h) and three constant temperatures of 25, 30 and 35°C. The type of functional response was affected by temperature. Type III functional response was determined for adult female of A. swirskii at 25°C, whereas type II was observed at 30 and 35°C. The longest handling time (Th) (0.6 ± 0.005) was observed at 25°C and the shortest handling time (0.46 ± 0.003) and higher attack rate (a) (0.56 ± 0.054) were observed at 35°C. Handling time (Th) decreased from 25 to 35°C. Temperature had a significant effect on the daily and total predation rates of each different stages: the predation rate increased from larva to adult and with temperature from 25 to 35°C, and the maximal value being reached at 35°C. The maximal predation capacity of female was about 40 eggs per day per females at 35°C. The results of this study showed the effect of temperature on functional response and predation rate of A. swirskii.